2016
DOI: 10.1039/c6fo01136e
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bactrocera oleae on phenolic compounds and antioxidant and antibacterial activities of two Algerian olive cultivars

Abstract: Bactrocera oleae, an olive fruit fly, is a major olive pest in Algeria. In this study, olives of two Algerian cultivars (Limli and Rougette de Métidja) with different degrees of infestation by the Bactrocera oleae fly (0%, not attacked; 100%, all attacked; and real %) were analysed. The influence of this pest on individual phenolic compounds (HPLC-DAD-FLD) and antioxidant profiles was ascertained. The antibacterial activity against 8 human enteropathogenic bacteria was also assessed. The results show that Roug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 43 publications
(48 reference statements)
1
4
0
Order By: Relevance
“…The decreased free-radical scavenging activity is probably due to the loss of polyphenols, flavonoids and o-diphenols (Mraicha et al, 2010). Other studies showed that the free-radical scavenging activity was positively correlated with the Vc concentration and total phenol content (Medjkouh et al, 2016). In this study, the phenol content and free-radical scavenging activity measured in orange juice decreased significantly after egg inoculation, which may indirectly indicate free-radical scavenging activity significantly decreased when Vc and phenol content decreased.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…The decreased free-radical scavenging activity is probably due to the loss of polyphenols, flavonoids and o-diphenols (Mraicha et al, 2010). Other studies showed that the free-radical scavenging activity was positively correlated with the Vc concentration and total phenol content (Medjkouh et al, 2016). In this study, the phenol content and free-radical scavenging activity measured in orange juice decreased significantly after egg inoculation, which may indirectly indicate free-radical scavenging activity significantly decreased when Vc and phenol content decreased.…”
Section: Discussionsupporting
confidence: 55%
“…These compounds have high biological activity and consequently, certain anti-oxidant, anti-inflammatory, anti-cancer and anti-bacterial activities in the human body (Naidu, 2003) as well as the ability to prevent cardiovascular diseases, diabetes and other ailments (Joshipura et al, 2001). The decrease in the total phenol content may be related to the enhanced activity of polyphenol oxidase and the effect of oxygen, which can enter the fruit pulp through the outlet hole produced by B. dorsalis larvae (Medjkouh et al, 2016). The phenolic substances decreased significantly after the infestation of B. dorsalis, and the content of these substances was less than 1/3 that of the control 10 days after egg inoculation, indicating that the intense chemical reaction inside the fruit resulted in the metabolism of phenolic substances with the growth and development of the larvae.…”
Section: Discussionmentioning
confidence: 99%
“…The reducing power of OVA samples was determined in accordance with the method of Medjkouh et al . with modifications.…”
Section: Methodsmentioning
confidence: 99%
“…Some research has found that lipid chain length and unsaturation are closely related to abiotic stresses in plants (14,23). To the best of our knowledge, no study has been published on the effects of lipid compositions other than fatty acids in response to biotic stress have been published (25)(26)(27). The current study found that oil extracted from infested oilseeds (Type C) contained significantly more long-chain lipids and unsaturated lipids than the two types of oils extracted from non-infested oilseeds (Type A and B).…”
Section: Discussionmentioning
confidence: 99%